THE ENGLISH TEACHERS’ COMPETENCIES IN ENGLISH FOREIGN LANGUAGE LEARNING AT MA MADANI ALAUDDIN PAO-PAO GOWA, SOUTH SULAWESI - Azhar, Nurul; Mardiana, Hj. (ETERNAL (English, Teaching, Learning, and Research Journal), 2016)
The objective of this research was to find out the of competencies of teachers in MA Madani Alauddin, Pao-Pao, which is only split into pedagogical and professional competence. The design of this research was qualitative descriptive. This research had two teachers as the subject.The data were collected through observation and interview. The researcher conducted a straight observation in the teaching and learning process of both teachers. In the classroom, the researcher matched what the teacher did with what observation list contained. Meanwhile, on this point, there are two types of interview, structured interview and unstructured interview. Structured interview was given to ask what teachers used to do in the classroom, in short, what they comprehend about professional and pedagogical competence. Unstructured interview was conducted by setting some students into the researcher talk in daily. Thus, it could fix about what the teacher did through the observation and their information with the students opinion. Furthermore, first, the pedagogical competence through the data gained between both teachers was in the deeply different level. One teacher, female, was not a favorite teacher due to her teaching style. It was gained through some interviews with students which was reverse to what the teacher displayed. While other teacher, male, was the favorite teacher due to the contrary to what the  previous teacher did. Overall, it was found that commonly students demanded the teacher extremely focused on what the students need like games which used to be forgotten by the teacher. As a whole they had been claimed as a professional teacher because they significantly concerned with things such as the mastery of material, the use of technology, and the professional continuity.